Low-Cost Schizandra chinesis Fruit Peel for Co(II) Removal from Aqueous Environment: Adsorption Properties and Mechanism - Reddy Koduru, Janardhan; Chang, Yoon-Young; Kim, Im-Soon (Asian Journal of Chemistry, 2013)
Biosorption is an ecofriendly wastewater treatment technique with high efficiency and low operating cost involving simple procedure for the removal and recovery of heavy metal ions from aqueous media. In present investigation, Schizandra chinesis fruit peel powder was utilized as biosorbent for the removal of Co(II) from aqueous media. The biosorbent was characterized by using Fourier transform infrared spectroscopy, scanning electron microscopy and energy dispersive X-ray techniques analysis. From FT-IR analysis it was found that hydroxyl, methoxy and carbonyl groups are involved in the removal of Co(II) from aqueous environment. The effect of various parameters for Co(II) removal by using Schizandra chinesis fruit peel powder are evaluated in batch biosorption method. Biosorption kinetics data was evaluated with kinetic models and the kinetic data was well fitted with pseudo-second-order kinetic model. The equilibrium data was in tune with the Langmuir isotherm model by revealing the maximum sorption capacity of 9.47 mg g-1 at pH 6.5, contact time 40 min. This study demonstrated that the Schizandra chinesis fruit peel powder biosorbent was a promising, efficient, economic and biodegradable sorbent.